Growth performance and nutrient uptake of pineapple (MD2) as influence by different rate of NPK green / Nur Nadhirah Razali - Razali, Nur Nadhirah (Faculty of Plantation and Agrotechnology, 2019)
The fruits production of pineapple is very responsive to NPK fertilization. However, the quality of pineapple will decrease with increasing of N application. It was reported that high N application level will decrease in Total Soluble Solid (TSS) and vitamin C of pineapple. Therefore, the aims of this study were to investigate the effects of different rate of NPK Green on early growth performance and nutrient uptake of pineapple (MD2). There are three different rates of NPK fertilizer was applied per plant which are 0 gram (T0), 20 gram (T1) and 40 gram (T2). Pineapples were planted on mineral soil and were designed in Randomized Completely Block Design (RCBD). The growth performance of pineapple MD2 such as leaf length, leaf number, leaf width and plant height were observed and measured until the 11th week. The uptake of macronutrient (P, K, Ca, Mg) and micronutrient (Fe, Al and Cu) were also analysed. The result shows that 20 gram (T1) of NPK green produce the highest growth performance compared to other rate of pineapple. The highest rate of fertilizer applied was result to high plant uptake. Application of 40 gram (T2) NPK green show the highest nutrient uptake for Total P (1443.83 mg/L) and K (11268.0 mg/L) while the result for micronutrient uptake it shows that 20 gram (T1) show the highest uptake for Al (653.38 mg/L) and Fe (366.01 mg/L). However, Analysis of variance (ANOVA) shows that there was no significant difference on growth performance and nutrient uptake among the rate of fertilizer (p≥ 0.05).